Microstructure formation in the Fe-based hardfacing alloy 5183 and its sliding wear behaviour in high temperature water - Carrington, Matthew John (2021)
Hardfacing alloys are used to minimise the tribological degradation of components subjected to sliding contact in the primary cooling systems of pressurised water reactors (PWRs). The combined effects of loaded sliding contact and corrosion within this environment (∼ 200 - 300 oC) currently require the extensive use of Stellite 6TM (Co-27-32%Cr-4-6%W-0.9-1.4%C in wt%). However, within the primary system, 59Co-based wear debris is transmuted to the γ-emitting 60Co which is hazardous for maintenance personnel. Therefore, significant efforts are being made to develop alternative Fe-based hardfacings manufactured by gas atomisation and powder (hot isostatic pressing) HIPing. Tristelle 5183 (Fe-21%Cr10%Ni-7.5%Nb-5%Si-2%C in wt%) is one of several Fe-based hardfacings that have been developed to reduce the dependence on Stellite 6. However, none of these alloys possess a tribological performance that matches that of Stellite 6. The development of new and improved Fe-based hardfacings is restricted by two factors. Firstly, an incomplete understanding of phase and microstructural evolution during their processing. Secondly, the mechanical deformation and tribological/chemical degradation mechanisms during sliding contact in a PWR environment are not sufficiently well understood. This thesis reports investigations into the microstructural evolution of HIPed Tristelle 5183 during processing and the tribological performance of both HIPed Tristelle 5183 and Stellite 6 over a range of temperatures in a simulated primary system PWR environment. These investigations give an improved understanding of tribological degradation within a primary system environment and provide insights needed for the development of future Fe-based hardfacings. This was made possible by using a bespoke tribometer which simulates a primary system PWR environment and microstructural characterisation techniques including, transmission electron microscopy (TEM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). Particular attention has been given to understanding the nanoscale aspects of subsurface microstructural evolution leading to degradation ii during sliding wear via the use of focused ion beam (FIB) produced site-specific lamellae and TEM. Phase and microstructure formation in gas atomised Tristelle 5183 is highly dependent on particle size and thus cooling rate during atomisation. Powder particles & 53 µm are principally composed of γ-Fe dendrites with smaller quantities of α-Fe, an interdendritic silicide phase and NbC. Powder particles . 53 µm also contain NbC and have increasing quantities of either dendritic α-Fe or cellular silicide phase; with decreasing amounts of γ-Fe as the particle size decreases. In contrast, HIPed Tristelle 5183 powder is principally composed of a γ-Fe solid solution matrix which surrounds both equiaxed Cr-based M7C3 (∼ 14.0 vol%) and Nb-based MX (∼ 9.6 vol%) precipitates, a small fraction of ferrite (∼ 1.0 vol%), and a π-ferrosilicide (∼ 0.3 vol%) phase. HIPing largely homogenises the microstructure, enables M7C3 precipitation and permits the decomposition of the metastable phases formed during atomisation. The tribological degradation mechanisms of self-mated HIPed Tristelle 5183 during sliding in lithiated water are sensitive to test temperature between 20 - 250 oC. The modes of plastic deformation at low strains were revealed by TEM to be highly dependent on matrix stacking fault energy and thus test temperature. However, at high strains extensive TEM showed that the subsurface is completely engulfed by strain localisation phenomena irrespective of test temperature and very large strains are accommodated via grain boundary mediated deformation mechanisms and crystallographic slip. At 20 oC, degradation principally occurs via plastic ratcheting wear; the extrusion of metallic slivers permits the formation of ductile shear cracks and the failure of these slivers generates plate/flake like wear debris. At 250 oC, degradation occurs via several mechanisms: (i) the breakdown of oxide-based tribofilms, (ii) wear enhanced corrosion, and (iii) corrosion enhanced plasticity-type wear. During the self-mated sliding contact of HIPed Stellite 6, the amount of material removal increases (16 - 39 times) between testing at 20 and 250 oC but the general degradation and deformation mechanisms largely remain the same. The deformation response of Stellite 6 is resistant to plastic strain localisation and iii the removal of material is confined to the nanoscale where the synergistic effects of the chemical degradation and mechanical deformation permit the removal of nanoscale particulates via tribocorrosion. A temperature dependent increase in corrosion rate and SFE are believed to be the principal factors influencing the temperature dependent increase in wear by tribocorrosion, although corrosion is believed to be the dominant factor.